ECONOMIC APPROACHES TO IMPROVE THE COMPETITIVENESS OF UKRAINIAN TRANSPORT ENTERPRISES ( THE EXAMPLE OF CIVIL AVIATION) - Baran, R. T. (Science and Transport Progress, 2010)
The purpose of reforming the air transport in Ukraine is the implementation of market economic transformations in economic and financial methods of the management of civil aviation operational firms, which were still formed on the basis of Soviet plan-army management principles. The author suggests the mechanism of formation of financial supply paradigm for reformed air transport firm because these reformations are to be carried out when the elaborated optimal economic-legal, investment-innovation, and (what is the most important) organizational-financial complex unified methodical principles of the interaction of air transport (АТ) subjects are absent (which becomes clear in the course of re-structuring them). Vital problems of formation of investment-innovation re-structuring mechanism for functioning the air transport firms are described in this article. New results of subsequent scientific research concerning financial scheme development of enterprising and commercial activities of airlines in today’s economic stabilization and growth, formation of new paradigm of economic theory and reformation of managing practice are suggested to the participants of the Conference in the course of prolonging the author’s discussion; a possible approach to the solution of financing problems for their re-structuring by means of creating new aviationtransport consortia is also suggested. The aim of creating a new consortium is to improve the economic efficiency of activity of airlines, their competitiveness in internal markets of transport services as well as to reform the system of air transport subjects in Ukraine. This is one of the complex trends for solving the problems of creating national air carrier, the organization of optimal forms and methods of financial schemes formation for measures aimed at improving the competitiveness.